The European Joint Research Project UHDpulse - Metrology for advanced radiotherapy using particle beams with ultra-high pulse dose rates - Schüller, Andreas; Heinrich, Sophie; Fouillade, Charles; Subiel, Anna; De Marzi, Ludovic; Romano, Francesco; Peier, Peter; Trachsel, Maria; Fleta, Celeste; Kranzer, Rafael; Caresana, Marco; Salvador, Samuel; et al. (Physica medica, 2020)
UHDpulse - Metrology for advanced radiotherapy using particle beams with ultra-high pulse dose rates is a recently started European Joint Research Project with the aim to develop and improve dosimetry standards for FLASH radiotherapy, very high energy electron (VHEE) radiotherapy and laser-driven medical accelerators. This paper gives a short overview about the current state of developments of radiotherapy with FLASH electrons and protons, very high energy electrons as well as laser-driven particles and the related challenges in dosimetry due to the ultra-high dose rate during the short radiation pulses. We summarize the objectives and plans of the UHDpulse project and present the 16 participating partners.
Keywords: lasery; Electrons; High dose rates; elektrony; částice - urychlovače; Lasers; celková dávka radioterapie; Dosimetry; radiometrie; Absorbed dose; vysokoenergetická radioterapie; protony; FLASH beams; Radiotherapy Dosage; European metrology project; Protons; Radiometry; Radiotherapy; radioterapie; Particle Accelerators; Radiotherapy, High-Energy; Traceability